Energy, exergy, environmental, and economic (4E) analyses of the usability of various nano-sized particles added lubricant in a heat pump system - Yildiz, Gokhan; Gurel, Ali Etem; Cingiz, Zafer; Agbulut, Umit (CELL PRESS, 2024)
The need for energy is rising significantly with the growth of technology in the world. This energy need is largely met by fossil fuels. The enhancement in their prices and the damage they induce to the environment, scientists have turned to alternative energy sources due to the depletion of fossil fuels. In recent years, these alternative energy sources have come to the fore as solar, wind, and wave energy. However, heating and refrigeration systems, whose share of energy consumption in buildings in the world is 40 %, can also compete with these alternative energy sources. In particular, heat pumps (HP) are at a level that can compete with renewable energy sources to seriously reduce this rate. In this study, different nanoparticles were added to the Polyol ester oil (POE) utilized in the compressor to enhance the performance of the HP. Thermodynamic, environmental, and economic performances of the obtained nanolubricants at different concentrations (0.5 wt% and 1 wt%) and flow rates (15, 30, and 45 g/s) were evaluated. The highest COP value of the HP was calculated as 4.14 at 0.5 wt% B-POE at 45 g/s. The best energy consumption in the HP was obtained with 0.5 wt% B-POE nanolubricant with a decrease of 10.96 % at 45 g/s compared to pure POE. The highest exergy efficiency in the HP was calculated at 0.5 wt% B-POE nanolubricant with a 13.53 % increase at 30 g/s compared to pure POE. The best exergoeconomic parameter (R-g,R-ex) performance was determined as 3.7148 kWh/$ in 1 wt% TiO2-POE nanolubricant at 45 g/s. The best enviro-economic value of 0.16182 cent/h was obtained with 0.5 wt% B-POE nanolubricant at 45 g/s. In line with the results obtained, it was observed that the B-POE nanolubricant has a performance that can compete with the good-performing TiO2-POE nanolubricant.
Keywords: Heat pump; Nanolubricant; Thermodynamics; Energy; Environment; THERMAL-CONDUCTIVITY; TIO2 NANOPARTICLES; PERFORMANCE; Science & Technology - Other Topics